2018
DOI: 10.1111/lam.12847
|View full text |Cite
|
Sign up to set email alerts
|

The expression of an exogenous ACC deaminase by the endophyteSerratia grimesiiBXF1 promotes the early nodulation and growth of common bean

Abstract: In this work, we studied the effect of ACC deaminase production by the bacterial endophyte Serratia grimesi BXF1, and its impact on the nodulation process of common bean. The results obtained indicate that ACC deaminase is an asset to the synergetic interaction between rhizobia and the endophyte, positively contributing to the overall legume-rhizobia symbiosis by regulating inhibitory ethylene levels that might otherwise inhibit nodulation and overall plant growth. The use of rhizobia together with an ACC deam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Strain MSR2 is able to produce increased levels of IAA, and possibly other phytohormones such as cytokinins (discussed below), that significantly impact the nodulation process (Miri et al, 2016;Nadzieja et al, 2018). In addition, strain MSR2 contains ACC deaminase activity, which facilitates the nodulation process of leguminous plants by decreasing inhibitory ethylene levels (Nascimento et al, 2016a;Nascimento et al, 2016b;Tavares et al, 2018;Nascimento et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…Strain MSR2 is able to produce increased levels of IAA, and possibly other phytohormones such as cytokinins (discussed below), that significantly impact the nodulation process (Miri et al, 2016;Nadzieja et al, 2018). In addition, strain MSR2 contains ACC deaminase activity, which facilitates the nodulation process of leguminous plants by decreasing inhibitory ethylene levels (Nascimento et al, 2016a;Nascimento et al, 2016b;Tavares et al, 2018;Nascimento et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…NER improve nodulation and N 2 fixation through different direct and indirect mechanisms, including production of one or more phytohormones, most often IAA, gibberellic acid and cytokinins (Bottini et al 1989;Hayashi et al 2014). In addition, they can increase nutrient (mainly P and Fe) availability in the root zone (Chebotar et al 2001;Argaw 2012), inhibit phytopathogens (Tavares et al 2018) and modify rhizosphere chemicals, such as ethylene (Nascimento et al 2018). The use of NER can significantly increase the ability of rhizobia resident in soil to form nodules, fix N and increase growth in soybean, Glycine max (Dashti et al 1998), mung bean (Shaharoona et al 2006), chickpea, Cicer arietinum (Abdiev et al 2019) and common bean (Chihaoui et al 2015).…”
Section: Legume-rhizobia-pgpr Interactionsmentioning
confidence: 99%
“…Inoculation of leguminous plants with ACC deaminase-producing rhizobia, inoculated singly or in consortia with free-living ACC deaminase-producing bacteria, leads to an increased nodulation phenotype (reviewed in Nascimento et al, 2016 ). By decreasing ACC levels these bacteria diminish the inhibitory ET concentrations that affect several phases of the nodulation process ( Ma et al, 2003 ).…”
Section: Counter Attack! Bacterial Modulation Of Plant Acc and Et Levmentioning
confidence: 99%
“…UW4, but not its acdS - mutant, increased the colonization of the arbuscular mycorrhizal fungus, Gigaspora margarita BEG9 in cucumber, leading to synergistic effects on plant growth ( Gamalero et al, 2008 ). Furthermore, several reports have shown that free-living rhizospheric bacteria with ACC deaminase activity readily promote the nodulation process of several leguminous plants ( Nascimento et al, 2016 ). These results indicate that the presence of bacteria with ACC deaminase activity can readily impact the colonization of other microorganisms present in the rhizosphere, including symbionts.…”
Section: Future Directionsmentioning
confidence: 99%